MUHZIN NAWAWI - PENGEMBANGAN KURIKULUM PENDIDIKAN BAHASA ARAB - Muhzin Nawawi Muhzin Nawawi (Institut Agama Islam Negeri (IAIN) Metro, 2017)
Arabic language has a very urgent position for Muslims, it is not only as a religious language (al-qur'an) but also as a science that needs to be developed through the development of its curriculum. The development of an Arabic language education curriculum is believed as a strategic way in the development and improvement of the quality of its education that ideally oriented towards of meeting the demands of development and also to respond to the challenges of globalization by still considering the proportionality both in the quantity and the quality of learning dimension in accordance with the formulated standards. The epistemology of Arabic science and its curriculum needs to be addressed and oriented to the formation of competitive maturity in today's global era. So the Arabic language education curriculum should ideally be developed integratively, holistically and humanistically. The education stakeholders should work sinergically to strengthen the Arabic language position, especially in the development of the Arabic language curriculum itself. The implication of that Arabic language graduations can realize three competencies, namely: linguistic, communicative, and socio-cultural competence in accordance with the demands of the times and become rahmatan lil ummah